TREN GLOBAL PENCARIAN INFORMASI KESEHATAN REPRODUKSI DI KALANGAN REMAJA: LITERATUR REVIEW - Sajdah Khusnul Mukhlis; Yuniar Wardani; Sitti Nur Djannah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Background: Pregnancy among adolescents rates are still relatively high worldwide, and adolescents' awareness of reproductive health is still low. Another significant issue is risky sexual conduct. Adolescents have more options to independently research topics on the internet and social media in the digital age. However, there are now more questions about the accuracy and quality of information found online. In order to create more successful interventions, this study intends to investigate global trends in teenagers' information-seeking behavior related to reproductive health. The types and sources of information that teenagers most frequently access on sexuality and reproductive health have not been extensively mapped in previous research studies. The formulation of a theme framework that identifies the most popular categories and resources of reproductive health information among adolescents is what makes this study new. This framework can be used to guide the creation of need-based sex education programs.Materials and Methods: This research used the PIOT method (Population, Issue, Outcome, and Type of research). A systematic literature search was conducted using the PubMed and ScienceDirect databases with the keywords “seeking information” AND “health reproduction” AND “sexsuality” AND “adolescent”. Studies employing qualitative interviews were selected due to the sensitive nature of the topic, allowing for deeper exploration of adolescents' experiences. Results: Results show that the most frequently used sources of information are schools, peers, and digital media. The most commonly sought topics include contraception, teenage pregnancy, sexuality, and puberty. Conclusion: he study underscores the need for multi-channel approaches that integrate digital tools with support from teachers and parents, tailored to adolescents’ cultural and social contexts.Keywords: Adolescent Reproductive Health, Information-Seeking Behavior, Global Perspectives, Adolescents.